2011
DOI: 10.1111/j.1740-0929.2010.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and utilization of genes associated with beef qualities

Abstract: The fatty acid composition of adipose tissue in beef has been recognized as an important trait because of its relationship with beef quality, including favorable beef flavor and tenderness. Over the last decade, we have tried to identify the genes responsible for the fatty acid composition in cattle, and have found the following. (i) Genetic polymorphism of stearoyl-CoA desaturase (SCD) is one of the responsible genes associated with fatty acid composition. The average effects of gene substitution of the SCD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 42 publications
(84 reference statements)
2
32
0
1
Order By: Relevance
“…This substitution has an effect on the fatty acid composition and melting point of intramuscular fat (IMF). Mannen (2011) confirmed that alanine compared to valine increases the proportion of monounsaturated fatty acids at the expense of saturated fatty acids and also decreases the melting point of IMF. Similar conclusions were reached by other authors (Taniguchi et al 2004;Matsuhashi et al 2011;Kaplanová et al 2013).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…This substitution has an effect on the fatty acid composition and melting point of intramuscular fat (IMF). Mannen (2011) confirmed that alanine compared to valine increases the proportion of monounsaturated fatty acids at the expense of saturated fatty acids and also decreases the melting point of IMF. Similar conclusions were reached by other authors (Taniguchi et al 2004;Matsuhashi et al 2011;Kaplanová et al 2013).…”
supporting
confidence: 64%
“…So the SCD gene can be marked as one of the genes responsible for fatty acid composition (Mannen 2011). According to Ohsaki (2009), the SCD gene has particular influence on the stearic acid and oleic acid presence in beef.…”
mentioning
confidence: 99%
“…Interestingly, in the livestock field, it is known as a key candidate gene for meat marbling, which is a phenomenon quite similar to muscle fatty infiltration 30, 31. Genetic ablation and pharmacological inhibition studies have shown that FABP4 plays a critical role in many aspects of the development of metabolic diseases and have suggested FABP4 as a therapeutic target for such diseases 29, 32, 33, 34.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that FABP4 is directly related to fatness traits and may be a potential marker for beef tenderness and intramuscular fat content (Michal et al, 2006;Jurie et al, 2007;Hoashi et al, 2008;Barendse et al, 2009;Lee et al, 2010;Mannen, 2011;Narukami et al, 2011;Zhao et al, 2012). However, the FABP4 gene function at the cellular level of cattle remains unclear.…”
Section: Introductionmentioning
confidence: 99%